The Role of Vocational Schools in Enhancing Teacher Competence for Inclusive Education of Special Needs Children in Central Kalimantan - Siti Juhairiah; Doddy Teguh Yuwono; Windari Sabela (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Background: This study aims to evaluate the effectiveness of training programs conducted by vocational schools in enhancing teacher competence for inclusive education of special needs children (SNC) in the Central Kalimantan region. Using a quantitative approach, a survey was conducted with 50 teachers from various schools in the region. The results of the study show that teachers' perceptions of the training effectiveness are generally positive, with an average rating of 3.9 out of 5. Data analysis reveals that teachers with longer teaching experience tend to have more positive perceptions of the training effectiveness. The main challenges identified in implementing skills from the training include a lack of time to prepare inclusive materials, limited resources, and inadequate support from school management. This research provides recommendations for the development of more specific and relevant training programs to meet teachers' needs, as well as increased support from school management to support the implementation of inclusive education. The results of this study are expected to make a significant contribution to improving the quality of inclusive education in Indonesia.